2004
DOI: 10.1016/j.lingua.2003.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Variation, ambiguity, and noun classes in English

Abstract: This paper explores a theory of the meaning-form relation based on ranked and violable constraints [A. Prince, P. Smolensky, 1993. Optimality Theory: Constraint Interaction in Generative Grammar, Rutgers University, New Brunswick, and University of Colorado, Boulder], using the English genitive construction as a testing ground. Our main thesis is that partially ordered optimality-theoretic grammars allow us to relate four apparently independent empirical phenomena: (i) categorical grammaticality contrasts; (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…the specific role of relational nouns (e.g. Löbner, 1985;Barker, 1995;Anttila and Fong, 2004) or deverbal head nouns (e.g. Grimshaw, 1990), as the empirical research reported in this article has not been conducted with an eye to such issues.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…the specific role of relational nouns (e.g. Löbner, 1985;Barker, 1995;Anttila and Fong, 2004) or deverbal head nouns (e.g. Grimshaw, 1990), as the empirical research reported in this article has not been conducted with an eye to such issues.…”
Section: Introductionmentioning
confidence: 97%
“…See e.g. the optimality-theoretic account byAnttila and Fong (2004), which predicts that the former more easily allow for a postnominal of-genitive than the latter. Thanks to a reviewer for pointing this out to me.19 Note that the overview inFig.…”
mentioning
confidence: 99%
“…The assumption of a stochastic generalization, i.e. the fact that this type of harmonic alignment does not need to be categorical but also allows for statistical preferences to be included in the model, was at the time a rather novel assumption within Optimality Theory and opened up this framework for any type of variationist work; see also O’Connor et al (2004) and Anttila & Fong (2004) for Optimality-Theoretic accounts of English genitive variation. Data from English genitive variation has consequently also been used to test for specific theoretical assumptions of Optimality Theory (Jäger & Rosenbach 2006).…”
Section: Interpretation: Making ‘Sense’ – Or: Embedding Findings Intomentioning
confidence: 99%
“…An exception to this generalization are possessive constructions with certain proper-noun locative possessors such as Angela Merkel of Germany , which translates into a corresponding s -genitive ( Germany's Angela Merkel ). This class of construction has received hardly any attention in the literature so far (but see Anttila & Fong 2004: 1255 and very recently Wolk et al 2013). In these constructions there is no initial definite article in the of -genitive construction because the proper-noun possessor does not require or even allow one, but the possessive construction is still definite and thus convertible into an s -genitive construction.…”
mentioning
confidence: 99%
See 1 more Smart Citation